Principal’s Leadership in Improving Teachers’ Ability to Implement the Merdeka Curriculum - Ambarwati, Sri; Ahyani, Nur; Rosani, Meilia (Journal of Social Work and Science Education, 2024)
This study aimed at improving teachers’ abilities at SD 83 Palembang in implementing the Merdeka Curriculum through training and mentoring. The study employed a classroom action research design.  The research subjects were the teachers at SD 83 Palembang. Data were collected through observation, interviews, and documentation. Data were analyzed using qualitative data analysis techniques. The research was conducted from April to May 2024 at SD 83 Palembang, involving 31 teachers and 9 educational staff as samples. The findings revealed that training and mentoring were effective in enhancing teachers’ capabilities in implementing the Merdeka Curriculum. The principal of SD 83 Palembang has fostered a positive school environment, evident in their active role in enhancing teachers’ competencies in implementing the Merdeka Curriculum. The Merdeka Curriculum grants schools and teachers greater autonomy in designing learning that aligns with students’ needs and potential. This necessitates teachers possessing adequate capabilities to effectively implement the Merdeka Curriculum.